A Conceptual Framework Of Entrepreneurial Orientation, Financial Literacy, And MSMEs Performance: The Role Of Access To Finance - Hamdana, Hamdana; Pratikto, Heri; Sopiah, Sopiah (Devotion : Journal of Research and Community Service, 2021)
This article intended to address a research vacuum by identifying the elements that impact MSMEs' financial performance, including the importance of access to finance, and establishing a conceptual framework that explains the link between these factors. The author proposed a building conceptual framework of MSMEs finance classic phenomena. A qualitative analysis approach may be used to establish and construct conceptual frameworks. This paper has combined knowledge from various relevant and reputable literature sources to build a conceptual model. If empirically verified, the suggested framework might be a viable option for supporting MSME owners in more successfully growing their businesses.